Challenges and Successes of a Multidisciplinary Pediatric Obesity Treatment Program. (December 2014) - Walsh, Stephanie M.; Palmer, Wendy; Welsh, Jean A.; Vos, Miriam B.
Background: Despite the well-documented need for multidisciplinary pediatric obesity treatment programs, few programs exist and best practices are not clearly defined. We describe the design and initial quality-related outcomes of the Strong4Life multidisciplinary pediatric obesity treatment program along with some challenges and solutions implemented over the first 2 years. The purpose of this report is to inform others interested in designing similar programs. Program Description : The Strong4Life Clinic obesity program was designed to provide children with the medical care, as well as the behavior change guidance and support needed to reverse their obesity and/or minimize the related health risks. This low-intensity program is designed to provide approximately 6 hours of care over 12 months from a medical provider, psychologist, registered dietitian nutritionist, exercise physiologist, and nurse. Results : Between August 2011 and February 2014, the Strong4Life clinic served 781 high-risk (mean sex- and age-adjusted body mass index [BMI] percentile 98.8) and racially/ethnically diverse (45% non-Hispanic black and 24% Hispanic) patients. Of the 781 patients seen, 66% returned for at least 1 visit. Nearly all returning Strong4Life patients stabilized or improved their BMI (90% of those who participated <6 months, 97% of those who participated 6 to <12 months, and 92% of those who participated ≥12 months). Conclusions : This report describes a low-intensity multidisciplinary weight management program that is feasible. Initial assessment of the program suggests benefit in most patients who participate >6 months, but longer follow-up and assessment of comorbidities are needed.